Penanganan Kenakalan Remaja Pecandu Napza Dengan Pendidikan Berbasis Kasih Sayang - Syukur Rahmatullah, Azam (Literasi: Jurnal Ilmu Pendidikan, 2013)
This research began when the writer interested to know depply about Suryalaya Islamic Boarding school with â€œPondok Remaja Inabah (Islamic  Boarding School â€œInabahâ€) that have succsed handle so many Victims of Narcotics addicted and teenagers/adolescent naughtiness that have applied during many years since 1970.  And recognized by Natioanl and also International. This is so clear that big/great achievement. Obviously Suryalaya Islamic Boarding school with â€œPondok Remaja Inabahâ€ is not left even compulsory using love and affection approach for the victims of narcotics addicted.This research is field research located in â€œPondok Remaja Inabah XV Putraâ€ or Islamic Boarding School Inabah XV for boys in Suryalaya Islamic Boarding School. The research subject are â€œabibahâ€ (designation for pupils or students)  took 10 pupils that represent; 3 student that to hesitate, 4 students that honest and  sincere, 4 students that compulsory when the first time come to Islamic Boarding School Inabah XV for boys. Keywords : Education using love